Penggunaan Media Literasi Kelas Awal di Sekolah Dasar - Elfia Sukma; Tin Indrawati; Ari Suriani (Universitas Negeri Padang, 2019)
The purpose of sending it to the community is to train teachers in using early grade literacy media in elementary schools. The method used in the form of training to teachers in using media literacy. Participants in the service are 18 Air Tawar Selatan elementary school teachers and 25 Air Tawar Selatan public elementary schools, 22 Koto Tangah District Padang City. Based on the training results it can be seen that the average score of the pre-test participants was 69.54 and the average value of reading poetry after the training was 78.18. Thus it can be seen that the ability of 18 Air Tawar Selatan public elementary school teachers and 25 Air Tawar Selatan public elementary school Koto Tangah District, Padang City have improved after the training in the use of early grade literacy media.